Fixed Point Results for Multivalued Mappings with Applications - Arshad Khan; Muhammad Sarwar; Farhan Khan; Habes Alsamir; Hasanen A. Hammad (Journal of Function Spaces)
In this manuscript, using the concept of multivalued contractions, some new Banach- and Caristi-type fixed point results are established in the context of metric spaces. For the reliability of the presented results, some examples and applications to Volterra integral type inclusion are also studied. The established results unify and generalize some existing results from the literature.